Analysis On Village Readiness In The Acceleration Of Open Defecation Free Achievement Status Based On Stimulus, Organism, And Response Approach - Rosanna, Siti Farihah; Ma'ruf, Khabib Fadlilatul; Aditya, Yogi; Nurika, Globila; Wikurendra, Edza Aria (Journal of Public Health for Tropical and Coastal Region, 2021)
Introduction: Open Defecation Free (ODF) is a condition in the community that has carried out total sanitation and does no more Open Defecation (OD). Dukuh Village was chosen as the research location because it was a village with the highest OD in Ngadiluwih, Kediri. This high rate of OD is caused by a lack of public awareness about the importance of sanitation. This research was conducted to analyze the village readiness to accelerate ODF status in Dukuh Village.Methods: This study was done in a qualitative method with a single holistic case study design using Stimulus-Organism-Response theory. The key informants of this study were five persons:1) the Head of Dukuh Village, 2) the environmental health officer of Wonorejo Community Health Center, 3) Dukuh Village community leader and 4) the community representatives who still defecated, and 5) no more defecated in an open area after triggering activities. They were selected purposively. Data were collected through in-depth interviews, Focus Group Discussion, and documents review. Data analysis was done through the Spradley model, scoring and categorizing village readiness using the scales of Aydin and Tasci.Results: Five main problems were the lack of funds for the ODF program, poor socialization, low Clean and Healthy Behavior, lack of roles from community leaders, and limited land for latrine construction. Based on the analysis of village readiness in achieving the ODF program using the Aydin & Tasci scale, the obtained score was 2.1. This score indicated that Dukuh Village was not ready yet and a lot of system improvements[h1]  were needed.Conclusion: Dukuh Village was not ready yet for the ODF program and need a lot of system improvements. It was recommended to make village policies, create working groups, and maximizing socialization.